The feminization of the judiciary in Portugal: dilemmas and paradoxes - Duarte, Madalena (2014)
In recent decades, a significant transformation in the legal professions has been its increasing feminization. However, if in other countries we can find relevant studies on this subject, the gender variable is rarely taken into account in Portugal, except through intuitive and non-scientific processes and discourses that often produce bias and where female judges and public prosecutors have no voice. This article aims to contribute to filling in this empirical lacuna and, based on a survey of the Portuguese population and on interviews with judges and public prosecutors in Portugal, to analyse the existing views on the feminization of justice and female judging.